Teacher Perceptions of Response to Intervention Implementation in Light of IDEA Goals - Jenkins, J. Kevin; Sekayi, Dia (Journal of the American Academy of Special Education Professionals, 2014)
Traditionally, school systems have identified students with specific learning disabilities (SLD) by a measured gap between achievement and ability in a specific area. Recent amendments to the IDEA allowed for the use of alternative methods of identifying students with a SLD. Some states have responded by using Response to Intervention (RTI). This new method represents a radical change in identification of SLD students. Consequently, policy makers need to know if RTI, as it is actually implemented, is serving the goals of the IDEA. Attempting to provide information on this subject, the authors conducted a modified Delphi study in a school system that requires RTI as the method of SLD identification. They analyzed the resultant data in light of the identified goals of IDEA. This article describes the research process employed, provides the aforementioned analysis, and draws conclusions and makes some initial recommendations for further research in this area.